Enhancing Energy Efficiency Through the Incorporation of Maqasid Syariah Knowledge: A Review - Mohd Zin Kandar; Nurul Hadirah Muszaffarsham; Elina Mohd Husini; Norita Md. Norwawi; Khairil Faizal Khairi (UiTM Press, 2024)
Vol.10.No.1 (2023) 171-190